PERANAN SISTEM INFORMASI E- CUTI UNTUK PEGAWAI DI LINGKUNGAN DITJEN BADILMILTUN - Atik Budi Paryanti; Sumarsid Sumarsid (Journal of Information System, Applied, Management, Accounting and Research, 2020)
The Directorate General of the Military Court and State Administrative Court or abbreviated to Ditjen Badilmiltun is one of the Organizational Units of the Supreme Court of the Republic of Indonesia. Based on this research paper, the writer conducted a systematic anaylyzing about leave of absence system in Ditjen Badilmiltun that in fact did not use the full advantages of information and technology.Employee who wants the information of leave of absence, the first thing they do is ask in employee resources development department and it will takes a long time to get the information or even to get the approvement of leave of absence. To solve that problem, the author took the initiative to design a online web based of leave of absence application. Online web based of leave of absence application, designed by using CodeIgniter, PHP and MySQL and for a User Interface using a tamplate from Bootstrap. This application provides information more easily and quickly to employees. Employees may apply for leave wherever and whenever they want so do approval of leave of absence by superiors and authorized officials.